Evaluating Knowing and Reasoning in College for Use in Christian Higher Education: $hErin M. Shaw - Shaw, Erin M. (Christian education journal, 2019)
This article evaluates Marcia B. Baxter Magolda's cognitive development theory in Knowing and Reasoning in College (1992) for its potential use in Christian higher education. Baxter Magolda is an educator and researcher who pioneered a study on cognitive development at Miami University. Her study considers both genders' perspectives on development. This article utilizes John David Trentham's principle of inverse consistency as a precedent to reorient Baxter Magolda's model to one consistent with a Christian worldview.